Situation Report: Hungary, 13 August 1974 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. A Case of Corruption Radical Simplification Proposed in Creation of Enterprise Funds Hungarian Foreign Trade: The Problems of Dynamism Government Protests EEC Embargo on Imports of Beef and Beef Cattle Coverage of Nixon Resignation No Wage Supplement for Agricultural Co-operative Members